Pengukuran Partisipasi Pria Dalam Ber-KB di Desa T onjong Puskesmas Kramatwatu - Sri Susanti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2018)
Increased male participation in family planning and reproductive health is part of the implementation of reproductive and reproductive health rights. The purpose of this research is to know the direct and indirect influence and ma gnitude of health promotion, social support, knowledge about contraception and attitudes toward male participation in family planning in Tonjong village Working Area of Kramatwatu Public Health Center 2015. The method used in this research is quantitativ e approach which uses a cross-sional design. The sample used is 70 respondents. The analytical method used is Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. The result of research hat male participation variable in family planning in Tonjong village Working Area of Kramatwatu Puskesmas is influenced by health promotion (26.14%), social support (11.03%), knowledge (12.4%) and attitude (26.51%). The direct influence of male participation in family planning in Tonjong village Working Area of Kramatwatu Health Center was 76.1% and indirect influence was 1.39%. Total direct and indirect influence of male participation in family planning was 77.5%. Suggestion of research need to pay attention to man (husband) who participate to use KB so that can increase the coverage of KB Men especially men (husband) who want to receive socialization about the importance of family planning Keywords : Support, Participation, Knowledge, Health Promotion, Attitude